Association between Systemic Immune‑Inflammation Index and Mortality in Type 2 Diabetes Patients Complicated with Ischemic Stroke: A Retrospective Cohort Study - Zhu, Hongwei; Shao, Guo (Trends in Immunotherapy, 2025)
Background: When type 2 diabetes mellitus (T2DM) occurs concomitantly with ischemic stroke, it poses a major challenge to global public health and is related to poor prognosis. Inflammation is a crucial factor driving the progression of this condition. The systemic immune-inflammation index (SII), which was considered capable of comprehensively assessing the overall immunity and inflammation, has a relationship with the mortality of T2DM patients suffering from ischemic stroke that has not yet been fully clarified. This study seeks to investigate the relationship between SII and mortality at 28 days and one year in T2DM patients complicated with ischemic stroke. Methods: The research utilized data from the MIMIC-IV database, with participants categorized into three groups based on SII tertiles. The primary outcome focused on mortality at 28 days and one year. The association between SII and mortality was assessed through smoothed curve fitting methods and multivariate Cox regression analyses. To analyse cumulative survival rates across these time frames, Kaplan-Meier curves were employed. Additionally, receiver-operating characteristic (ROC) curves were generated to gauge the predictive capabilities of SII. To ensure the reliability of the findings, subgroup analyses were performed. Results: This study evaluated a total of 1,204 patients. The results indicated that an increase in SII correlated with an increased likelihood of mortality at both 28 days and one year among individuals with T2DM complicated by ischemic stroke. Higher levels of SII were significantly linked to an elevated hazard ratio for 28-day (HR: 1.43, P<0.01) and 1-year (HR: 1.27, P<0.01) mortality in this patient group. A nonlinear relationship between SII and mortality in this patient population was evident from the smoothed fitting curve (P<0.01). The ROC analysis demonstrated that SII outperformed both the SOFA and GCS scores in predicting mortality in this patient population. The decision curve analysis reinforced that SII offered a superior net benefit compared to the SOFA and GCS scores. Subgroup analyses showed no significant interaction between SII and all subgroups (P value of interaction >0.05). Conclusion: In T2DM patients with ischemic stroke, higher SII levels correlated with increased mortality at 28 days and one year.